Valoración del riesgo de desarrollar Diabetes Mellitus Tipo 2 en los habitantes del barrio “La Pradera” - Cuenca Celi, Leidy Salome (2023)
Diabetes Mellitus type 2 is a chronic non-communicable disease of multiple causal factors, it is characterized by resistance and insufficient production of insulin, there are also alterations in the incretin system which results in changes in the metabolism of fats and proteins. There are several modifiable and non-modifiable risk factors that can influence the development of the disease; with the objectives of analyzing the risk of developing type 2 Diabetes mellitus in the inhabitants of the "La Pradera" neighborhood, identifying age groups with a higher risk of the disease, establish the risk factors that have the highest incidence, and thus develop actions to prevent the risk of presenting the disease. A quantitative, descriptive, cross-sectional study was developed with a sample of 354 people from the “La Pradera” neighborhood and the use of the Findrisk screening test allowed us to evaluate the risk of developing type 2 Diabetes. It was evident that the study population presented low risk of developing diabetes in 10 years with 39% of the total population, however, a minimum percentage presented high risk; Likewise, half of the research participants do not do physical activity, do not consume fruits and are overweight; finally, 47% of the population has a second-degree family history of Type 2 Diabetes Mellitus. It is concluded that in the La Pradera neighborhood the The risk is low to develop type 2 Diabetes mellitus in 10 years, the age group with high risk was 54 to 64 years, with a higher incidence of modifiable factors